Kisar, a small island participant in an extensive maritime obsidian network in the Wallacean Archipelago. (September 2019) - Reepmeyer, Christian; O'Connor, Sue; Mahirta,; Kealy, Shimona; Maloney, Tim
Abstract: Here we report the results of a pXRF analysis of obsidian stone artefacts from Here Sorot Entapa rockshelter (HSE) on Kisar Island in the Wallacean Archipelago. With the exception of a single flake, all the obsidian artefacts in this site are from a single source. Kisar has a metamorphic geology with fringing uplifted limestone terraces which makes obsidian raw material exotic to the island. The Kisar obsidian is a chemical match to obsidian of an unknown source previously recovered from sites in Alor Island to the west, and which also appears in Timor Leste to the south. The obsidian results suggest that Kisar was receiving exotic obsidian from 15, 000 years ago, and was linked with Alor and Timor in a maritime interaction network from at least 13, 000 years ago.